Предмет: Математика,
автор: Mirashi
Напиши сумму двух выражений и упрости ее:
— 4,5 — m и 27,2 + m
Приложения:
Ответы
Автор ответа:
1
Ответ:
22,7
Пошаговое объяснение:
(-4,5 - m) + (27,2 + m) = -4,5 - m + 27,2 + m = -4,5 + 27,2 = 22,7
- m + m = 0
Автор ответа:
1
Ответ
22,7
Пошаговое объяснение:
(27,2+m)-(4,5+m)=27,2-4,5+m-m=27,2-4,5=22,7
Похожие вопросы
Предмет: Русский язык,
автор: irinakna
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: asyakoval2004
Предмет: Физика,
автор: Hokkaido